Cardiomyocyte-specific RXFP1 overexpression protects against pressure overload-induced cardiac dysfunction independently of relaxin - Wingert, Julia; Meinhardt, Eric; Sasipong, Nuttarak; Pott, Marcel; Lederer, Christoph; Torre, Carolina de la; Sticht, Carsten; Most, Patrick; Katus, Hugo; Frey, Norbert; Raake, Philip; Schlegel, Philipp (Biochemical pharmacology, 2024)
Heart failure (HF) prevalence is rising due to reduced early mortality and demographic change. Relaxin (RLN) mediates protective effects in the cardiovascular system through Relaxin-receptor 1 (RXFP1). Cardiac overexpression of RXFP1 with additional RLN supplementation attenuated HF in the pressure-overload transverse aortic constriction (TAC) model. Here, we hypothesized that robust transgenic RXFP1 overexpression in cardiomyocytes (CM) protects from TAC-induced HF even in the absence of RLN. Hence, transgenic mice with a CM-specific overexpression of human RXFP1 (hRXFP1tg) were generated. Receptor functionality was demonstrated by in vivo hemodynamics, where the administration of RLN induced positive inotropy strictly in hRXFP1tg. An increase in phospholamban-phosphorylation at serine 16 was identified as a molecular correlate. hRXFP1tg were protected from TAC without additional RLN administration, presenting not only less decline in systolic left ventricular (LV) function but also abrogated LV dilation and pulmonary congestion compared to WT mice. Molecularly, transgenic hearts exhibited not only a significantly attenuated fetal and fibrotic gene activation but also demonstrated less fibrotic tissue and CM hypertrophy in histological sections. These protective effects were evident in both sexes. Similar cardioprotective effects of hRXFP1tg were detectable in a RLN-knockout model, suggesting an alternative mechanism of receptor activation through intrinsic activity, alternative endogenous ligands or crosstalk with other receptors. In summary, CM-specific RXFP1 overexpression provides protection against TAC even in the absence of endogenous RLN. This suggests RXFP1 overexpression as a potential therapeutic approach for HF, offering baseline protection with optional RLN supplementation for specific activation.
Online verfügbar: 19. Mai 2024, Artikelversion: 28. Mai 2024
Gesehen am 26.11.2024